Exploration of Spiritual Elements in Holistic-Entrepreneur (Holistic-E): Student Development Perspectives - N.H, Mohamad; A, Selamat; ., . (International Journal of Engineering and Technology, 2018)
The Entrepreneurship is seen as a potential career path for overcoming the problem of unemployment. However, this career has yet to get a second or even a last option among graduates in Malaysia. Government has introduced several initiatives to cultivate entrepreneurial spirit among students or graduates such as the first surge of the Malaysia Education Blueprint 2015-2025 (Higher Education) and Entrepreneurship Action Plan 2016-2020. Despite the magnitude of these efforts, little is known whether graduates today are entrepreneurial. Furthermore, based on current achievements, this is quite difficult to implement as the desire of graduates in entrepreneurship is not particularly encouraging, especially graduates in technical courses. Compared to previous studies on student development that only examines the external element of the student affecting entrepreneurial desires, this study focuses on the internal elements of students holistically to increase student entrepreneurial desires and improve entrepreneurship as one of the preferred careers in Malaysia in meeting the challenges of the first shift of the Malaysia Education Blueprint 2015-2025; produce more graduate entrepreneurs.Â Â